2008
DOI: 10.12693/aphyspola.114.455
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Topographic Studies of Defect Structure in YVO4Crystals

Abstract: The perfection of YVO4 crystals, which are predicted to replace formerly used YAG garnets due to higher quantum efficiency and lower excitation level, was studied. The investigations of Czochralski grown undoped YVO 4 single crystals were performed mainly by means of X-ray topographic methods. Both synchrotron and conventional X-ray sources were used. The study revealed relatively high density of weak point-like contrasts which can be most probably interpreted as dislocation outcrops. In regions of the crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
3
9
0
Order By: Relevance
“…Comparing the results with the ones obtained for YVO 4 undoped crystals, presented by Wieteska et al [8] we can see that block structure is more distinct in doped crystals than in undoped ones.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Comparing the results with the ones obtained for YVO 4 undoped crystals, presented by Wieteska et al [8] we can see that block structure is more distinct in doped crystals than in undoped ones.…”
Section: Discussionsupporting
confidence: 67%
“…[1][2][3][4][5][6][7][8]. The main difficulty in the applications is obtaining of the crystals with low concentration of defects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). The same result was observed for another samples studied earlier [8][9][10][11][12][13][14][15]. In the outer part of these crystals a lot of linear black diffraction contrasts and volume defects contrasts of irregular shapes were observed.…”
Section: Resultssupporting
confidence: 86%
“…The results of our previous studies concerning SLG crystals were shown in Refs. [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%